Impact of type 2 diabetes on oncologic outcomes of hepatocellular carcinomas in non-cirrhotic, non-alcoholic steatohepatitis: a matched-pair analysis - Billeter, Adrian; Müller, Philip C.; Albrecht, Thomas; Rössler, Stephanie; Löffler, Moritz; Murtha-Lemekhova, Anastasia; Mehrabi, Arianeb; Müller, Beat P.; Hoffmann, Katrin (Journal of gastrointestinal surgery, 2021)
Non-alcoholic steatohepatitis (NASH) associated hepatocellular carcinomas (NASH-HCC) are increasing. NASH-HCC often develops in the fibrotic liver. Several analyses report conflicting results regarding the outcome of non-cirrhotic NASH-HCC. Furthermore, type 2 diabetes (T2D) is considered a risk factor for poor survival. The aim of this study was to investigate oncological outcomes of non-cirrhotic NASH-HCC and the impact of T2D.